Quanfima: An open source Python package for automated fiber analysis of biomaterials; PLoS One; Vol. 14, iss. 4 - Shkarin R. Roman; Shkarin A. Andrei; Shkarina S. N. Svetlana Nikolaevna; Cecilia A. Angelica; Surmenev R. A. Roman Anatolievich; Surmeneva M. A. Maria Alexandrovna (2019, 2019)
Title screen